SHORT MOVIE PRODUCTION TO ENCOURAGE ASIAN DIGITAL NATIVES TO SPEAK ENGLISH - Rahmah, Nur Alfa; Sari, Afifah Linda (English Department of Faculty of Tarbiyah and Teacher Training, 2018)
Speaking in foreign language is a productive skill that requires not only sufficient language input and communication strategy, but also a lot of practices and experiences. Students who cannot fulfill all those requirements might get problems during speaking, especially those who have low confidence level, insufficient communication skill, lack of vocabulary and lack of automaticity. Students often hesitate during speaking too because they are afraid of making mistakes, losing face and criticism. Such problems are commonly found among English learners in Asia, especially where English is a foreign language and access to English natural environment and English daily practices is extremely limited. Certain teaching strategies are then needed to overcome these obstacles; one of them is movie production. This study views teenage students in Asia as digital natives that can take a lot of benefits from technology to improve their English and make English language part of their life even though they do not live in natural English environment. Through movie production, students get freedom of expression without feeling anxious that they are being formally graded. It is fun and challenging and explores their language creativity; they can rehearse as much as they want; consult the dialogue to their teachers; and correct their mistakes and learn from it. In brief, this task integrates many communication skills needed in speaking, improves their confidence, and gives them real experience and a lot of practice. The movie can as well be evaluated to assess students' progress in speaking.